TRANSFORMATION OF HADITH EDUCATION IN INDONESIA;: Methods, Scholarly Authority, and Technology from Sorogan to Artificial Intelligence (AI) Tutor - Zulfarizal; Indal Abror; Muhammad Abdul Kharis (STAIN Majene, 2026)
This article examines the evolution of hadith education in Indonesia by highlighting the transformation of learning methods, the shift in scholarly authority, and the role of technology, from the sorogan and bandongan traditions to the use of e-learning and AI tutors. Hadith education has historically relied on a direct relationship between teacher and student, emphasizing the transmission of sanad (chain of transmission), scholarly authority, and the internalization of knowledge. However, the development of digital technology has presented new forms of hadith learning that are more open, rapid, and personalized, while simultaneously contradicting traditional patterns of authority. Through a qualitative approach with historical-conceptual analysis and a literature review, this article demonstrates that the transformation of hadith education in Indonesia is not linear, but rather a continuous process of adaptation between tradition and technological innovation. AI tutors and digital platforms, while offering efficiency, have not been able to completely replace the authoritative, ethical, and spiritual dimensions of hadith education. These findings clarify that the relevance of hadith in modern discourse lies not in the rejection of technology, but rather in the ability of the hadith education tradition to critically adapt technology without losing its epistemic foundation and scholarly authority.